SYNTHESIS AND IR SPECTROSCOPIC STUDY OF FERROCENE CONTAINING COMPLEX COMPOUNDS (Scientific journal of the Fergana State University, 2024)
As a result of the interaction of monocarboxylic acid hydrazides and ferrocenoylacetone, hydrazones (H2L) and transition metal complexes based on them were synthesized. The IR spectra of the obtained compounds were studied. The IR spectra of the synthesized compounds were studied. The research results showed that H2L in solution exists in the form of a tautomeric mixture: hydrazone, α-hydroxyazine and cyclic 5-hydroxypyrazoline forms. According to the results of IR spectra, the complexes are assigned a planar-square structure and in them the doubly deprotonated ligand residue is coordinated by a metal atom through two oxygen atoms and a nitrogen atom of the hydrazone fragment. The fourth place in the flat square of the trans-N2O2 coordination site is occupied by an ammonia molecule.